pengaruh kualitas pelayanan dan kepuasan pelanggan pada jasa kirim j&t expres: pengaruh kualitas pelayanan dan kepuasan pelanggan pada jasa kirim j&t expres - Haedar Haedar; Tia Juliawati; Harmi Harmi (Universitas Slamet Riyadi, 2024)
J&T Express is a company operating in the field of goods delivery services operating in Indonesia, which was founded on August 20 2015. This research aims to determine the effect of service quality and customer satisfaction on J&T Express delivery services. The quality of delivery services has an important position in creating customer satisfaction. Providing satisfaction to customers is one of the factors of service quality, this is defined as a negative influence when service quality is below standard, because it can cause minimal customer satisfaction with the service they receive. This research method uses quantitative methods. The population in this research are users of J&T Express expedition services. A sample of 33 respondents was taken using saturated sampling technique. The data used in this research is primary data in the form of a questionnaire. The focus of this research is the Influence of Service Quality and Customer Satisfaction on J&T Express Delivery Services. Determining the influence of J&T Express service quality on customer satisfaction is the aim of this research.